TINGKAT EMOTIONAL WELL-BEING TERHADAP MAHASISWA DISABILITAS DI UNIVERSITAS NEGERI PADANG - Hedesti, Wulan; Marlina, Marlina (Jurnal Manajemen Pendidikan, 2025)
Emotional development in people with disabilities will have an impact on their ability to interact with the surrounding environment so that they can adjust well. This research was raised because the level of emotional well-being of students with disabilities who study at Padang State University is not yet known. The subjects in this study were 56 UNP students with disabilities from the class of 2017-2023 who came from various different study programs. In this study, the method used was descriptive research with a quantitative approach. The data collection technique uses an online questionnaire via Google Form which is distributed on social media. the research instrument uses the Emotional Well-Being scale. The results of this study that the level of emotional well-being in students with disabilities at Padang State University then obtained the results in general 27 (48.2%) students with disabilities at Padang State University were in the high category, 29 (51.8) students with disabilities at Padang State University were in the medium category and 0 (0%) students with disabilities at Padang State University were in the low category. Based on the analysis of each aspect, it is known that the satisfaction aspect obtained a value of 23.95%, happiness with a value of 21.32%, and optimism is at a value of 17.71%.